2015
DOI: 10.1039/c4ra12150c
|View full text |Cite
|
Sign up to set email alerts
|

Icephobic/anti-icing potential of superhydrophobic Ti6Al4V surfaces with hierarchical textures

Abstract: The icephobic potential of hierarchical superhydrophobic surfaces, which were prepared by modifying micro-nanostructures (constructed by the combination of sand blasting and hydrothermal treatment) on the surfaces of Ti6Al4V alloy with fluoroalkylsilane, was investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(50 citation statements)
references
References 43 publications
1
49
0
Order By: Relevance
“…[ 87 ] The hierarchical superhydrophobic surface exhibited excellent anti-wetting property with a static contact angle of 161° and dynamic sliding angle of 3°. They concluded that the icing-delay time on the superhydrophobic rough surface was many times longer than that on the smooth hydrophilic counterpart, and the ice adhesion strength on superhydrophobic surface was greatly reduced due to the Cassie wetting state with minimum contact areas.…”
Section: Anti-fogging/anti-icing/anti-corrosionmentioning
confidence: 99%
“…[ 87 ] The hierarchical superhydrophobic surface exhibited excellent anti-wetting property with a static contact angle of 161° and dynamic sliding angle of 3°. They concluded that the icing-delay time on the superhydrophobic rough surface was many times longer than that on the smooth hydrophilic counterpart, and the ice adhesion strength on superhydrophobic surface was greatly reduced due to the Cassie wetting state with minimum contact areas.…”
Section: Anti-fogging/anti-icing/anti-corrosionmentioning
confidence: 99%
“…31 The CCD camera was also used to record the contact process of an impact droplet to the surfaces of these samples, and the contact time was directly obtained from the CCD camera. The icing-delay time can be directly obtained from the CCD camera.…”
Section: Characterizations and Anti-icing Potential Testmentioning
confidence: 99%
“…Moreover, Sample 3 exhibits a higher icing-delay performance than Sample 2, because the microscale array patterns with the nanohair structures favors to trap more air pockets between the droplet and solid surface, as revealed in Fig. 31 According to the wetting models of the droplet on these surfaces, the ice adhesion strength is mainly depended on the contact area fractions (f 1 ) of the liquid droplet on the solid. Although superhydrophobic surfaces have a strong icingdelay performance, the ice growth still occurs aer a certain amount of freezing time in subzero environment.…”
Section: Anti-icing Potentialmentioning
confidence: 99%
“…A common superhydrophobic surface can embody antifreezing, self-cleaning, and anti-drag properties only in water [1][2][3][4], but may not be repellent to other liquids. To solve this problem, researchers have started to concentrate on studying the fabrication of superhydrophobic surfaces that can resist multiple liquids [5][6][7].…”
Section: Introductionmentioning
confidence: 99%